Pengaruh Social Media Marketing Activities dan E-Wom melalui Brand Awareness terhadap Purchase Intention Produk Parfum HMNS - Isfahana Nursyahbani; Sisca Debyola Widuhung (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The rapid growth of internet usage has significantly impacted consumer habits, changing their behavior in various ways. Correspondingly, this evolution has also transformed social media from a communication platform to a marketing tool. Nowadays, social media marketing activities and electronic word of mouth play an important role in growing brand awareness which significantly influences consumer purchase intention. Using the theory of planned behavior, this study aims to analyze the direct and indirect effects of social media marketing activities, electronic word of mouth, and brand awareness on purchase intention with a focus on the HMNS perfume brand in Banten. This research uses a quantitative approach, with a sample of 140 respondents of Banten population. The software used in this study is Smart-PLS to test the proposed hypothesis. The results of this study reveal that social media marketing activities and electronic word of mouth have a positive effect on brand awareness, electronic word of mouth and brand awareness have a positive effect on purchase intention. However, the effect of social media marketing activities does not significantly affect purchase intention. The results of this study provide valuable benefits for companies in this industry to develop effective marketing strategies to be successful in a highly competitive market. This study suggests that managers maximize the potential of social media marketing to increase brand awareness, which has a positive impact on purchase intention.